"Winning and losing": vulnerability to mass marketing fraud. Issue 6 (14th December 2015) - Olivier, Sean; Burls, Trish; Fenge, Lee-Ann; Brown, Keith
Abstract : Purpose: – The purpose of this paper is to report the findings from a small qualitative study of victims of mass marketing fraud (MMF), exploring how they become involved in such activity and then sustain their involvement. The paper concludes with recommendations for practitioners involved in supporting vulnerable older people. Design/methodology/approach: – The paper considers a small qualitative case study into the vulnerability of older people ( n =3) to MMF from the perspectives of the "victims" of such fraud. Findings: – This paper highlights a range of predisposing risk factors to MMF which emerged as key themes including the psycho-social background of the victim, emotional vulnerability, the need for meaningful activity and opportunities engagement in meaningful social activity. Research limitations/implications: – The small scale of this research is a limitation, but as there is currently a dearth of research in this area it makes a valuable contribution to the developing knowledge base. Practical implications: – Professionals need to develop increased understanding of the complexities of sustained involvement in MMF, and the ways in which fraudsters manipulate potential victims by "grooming" and luring through plausible schemes which appear genuine to the victim. Social implications: – MMF is a growing threat in the financial abuse of older people, and is increasingly recognized as a concern for professionals involved in supporting and safeguarding vulnerable older people. Originality/value: – Despite the growing awareness of MMF in the financial abuse of vulnerable older people, this paper is one of the first to consider the perspectives of victims of MMF.